Confirmation of guideline‐defined hepatitis C screening strategies within the ‘Check‐Up35+’ examination in the primary care setting - Petroff, David; Wolffram, Ingmar; Bätz, Olaf; Jedrysiak, Katrin; Kramer, Jan; Berg, Thomas; Wiegand, Johannes (Liver international, 2023)
Background and Aims Screening strategies for undiagnosed infections are fundamental for hepatitis C virus (HCV) elimination. We previously investigated HCV prevalence and screening strategies in an urban primary care setting. IV drug abuse, blood transfusion before 1992, immigration, or elevated ALT were identified as risk factors in a post hoc analysis and diagnosed 83% of unknown HCV‐RNA‐positive cases by screening only 26% of the population. We aimed to validate prospectively the proposed screening algorithm in two independent urban and rural cohorts and to analyse for potential differences. Methods Anti‐HCV and ALT were included in a routine check‐up together with a questionnaire covering risk factors. HCV‐RNA was analysed in anti‐HCV‐positive individuals. Results In urban and rural areas, 4323 and 9321 individuals were recruited. The anti‐HCV prevalence was 0.56% and 0.49%, and 0.1% of patients were HCV‐RNA‐positive in both regions. Fifty‐two anti‐HCV positive patients including eight HCV‐RNA‐positive cases were unaware of the infection (number needed to screen to detect one unknown anti‐HCV‐positive individual: 262). At least one of the three aforementioned risk factors or elevated serum ALT was present in 3000 patients (22%). Restricting HCV screening to only those with risk factors, 52% and 75% of all anti‐HCV and HCV‐RNA‐positive undiagnosed patients were identified (number needed to screen: 111). Conclusions We confirm prospectively the efficiency of a risk‐based HCV screening. The risk‐based algorithm should be evaluated in other countries with similarly low HCV prevalence as in Germany to achieve WHO HCV elimination goals.